KURIKULUM PENGAJARAN KOSAKATA BAHASA ARAB UNTUK MAHASISWA KEPERAWATAN TINGKAT PEMULA DI UNIVERSITAS MUHAMMADIYAH MAHAKARYA ACEH BERBASIS ACTFL - Leni Marliana; Maisura Maisura (Yayasan Haiah Nusratul Islam, 2024)
This research aims to design and implement an Arabic vocabulary teaching curriculum based on ACTFL (American Council on the Teaching of Foreign Languages) for entry-level nursing students at Muhammadiyah Mahakarya University, Aceh. An ACTFL-based approach was chosen to ensure that learning Arabic does not only emphasize understanding grammar, but also effective communication skills in a clinical context. This research method involves curriculum development stages which include needs analysis, material design, implementation, and evaluation of curriculum effectiveness. The research subjects consisted of 30 entry-level nursing students who took part in a learning program for one semester. Research instruments include pre-test and post-test to measure vocabulary improvement, questionnaires to assess student satisfaction, and observations to assess engagement and interaction in class. The research results showed that the ACTFL-based curriculum significantly increased mastery of Arabic vocabulary relevant to nursing among students. The pre-test and post-test showed an average increase in scores of 45%, while the satisfaction questionnaire showed 90% of students felt more confident using Arabic in clinical contexts. Class observations show that communicative and interactive learning methods encourage active student participation. The ACTFL-based Arabic vocabulary teaching curriculum is effective in improving nursing students' communication skills in clinical situations. Recommendations from this research include expanding the implementation of this curriculum to other nursing study programs and further developing learning materials for advanced levels.